Low circulating soluble interleukin 2 receptor level predicts rapid response in patients with refractory rheumatoid arthritis treated with infliximab. Issue 1 (7th June 2005) - Kuuliala, A; Nissinen, R; Kautiainen, H; Repo, H; Leirisalo-Repo, M
Abstract : Background: Treatment with infliximab induces a rapid therapeutic response in most patients with active rheumatoid arthritis. Factors predicting good response are not well known. Objective: To study the predictive value of baseline level of soluble interleukin 2 receptor (sIL2R), a marker of lymphocyte activation, on the treatment response. Methods: 24 patients with active rheumatoid arthritis received intravenous infusions of infliximab at study entry, at two weeks, at six weeks, and at eight week intervals thereafter. Outcome was evaluated at six weeks and 22 weeks. Clinical assessment and standard laboratory tests were made and the DAS28 disease activity score was calculated. Serum sIL2R level at entry was measured by automated immunoassay analyser (Immulite®). The mean change in DAS28 score from entry to six weeks and 22 weeks was calculated and related to sIL2R level using baseline adjusted robust regression analysis. Results: Baseline level of serum sIL2R (mean (SD), 621 (325) U/ml) did not correlate with baseline DAS28 score ( r  = 0.24 (95% confidence interval, −0.18 to 0.58)). At six weeks DAS28 scores improved, with a mean change of −2.53 (−3.08 to −1.98) (p<0.001). This change was predicted by low baseline sIL2R level (regression coefficient per 100 U/ml: 0.205 (0.003 to 0.407) (p = 0.047)). At 22 weeks the DAS28 scores improved, with a mean change of −2.26 (−2.75 to −1.77) (p<0.001). The change was not predicted by baseline sIL2R level. Conclusions: Low baseline sIL2R level may predict a rapid clinical response in patients with refractory rheumatoid arthritis treated with infliximab.